Perancangan Model Referral dengan Pendekatan Design Science Research Methodology - Linda, Mei; Imbar, Radiant Victor (Maranatha University Press, 2024)
This research aims to create an effective referral model by applying the Design Science Research Methodology (DSRM) in the context of case X. This methodology focuses on integrating theory and practice to produce innovative solutions. By using this approach, the research proposes a model based on a theoretical framework that has proven effective. Data collection was conducted through surveys, interviews, and direct observation. The main focus of this research is the development of a model that not only enhances efficiency in the referral process but also improves service quality for stakeholders. The final results of the research include supporting artifacts for the solution development process, such as PRDs and flowcharts. It is hoped that the results of this study will provide practical guidance for companies or organizations facing challenges in managing complex referral processes. Therefore, this research is expected to make a significant contribution to the development of efficient and effective referral systems.